Towards achieving the fast-track targets and ending the epidemic of HIV/AIDS in Ethiopia: Successes and challenges. (January 2019) - Assefa, Yibeltal; Gilks, Charles F.; Dean, Judith; Tekle, Betru; Lera, Meskele; Balcha, Taye Tolera; Getaneh, Yimam; Van Damme, Wim; Hill, Peter S.
Abstract: Background: Ethiopia has adopted the global plan to end the epidemic of HIV/AIDS. The aim of this study was to assess the progress made towards achieving this plan. Methods: A review and analysis of national population-based surveys, surveillance, and routine programme data was executed. The data analysis was conducted using Excel 2016 and Stata 14 (StataCorp LP, College Station, TX, USA). Results: Between 2011 and 2016, the number of HIV-related deaths dropped by 58%, while that of new HIV infections dropped by only 6%. Discriminatory attitudes declined significantly from 77.9% (95% confidence interval (CI) 77.3–78.4%) in 2011 to 41.5% (95% CI 40.6–42.4%) in 2016. Around 79% of adult people living with HIV (PLHIV) were aware of their HIV status; 90% of PLHIV who were aware of their HIV status were taking antiretroviral treatment (ART) and 88% of adult PLHIV on ART had viral suppression in 2016. The proportion of people aged 15–49 years who had ever been tested for HIV and had received results increased from 39.8% (95% CI 39.2–40.4%) in 2011 to 44.8% (95% CI 44.2–45.4%) in 2016. This proportion was very low among children below age 15 years at only 6.2% (95% CI 5.9–6.5%). Among regions, HIV testing coverage varied from 13% to 72%. Female sex workers had lower coverage for HIV testing (31%) and ART (70%) than the national average in the adult population. International funding for HIV dropped from more than US 1.3 billion in 2010–2012 to less than US 800 million in 2016–2018. Conclusions: Ethiopia is on track to achieve the targets for HIV testing, ART, viral suppression, and AIDS-related deaths, but not for reductions in new HIV infections, discriminatory attitudes, and equity. Ending the epidemic of HIV/AIDS requires a combined response, including prevention and treatment, tailored to key populations and locations, as well as increased funding.